Protective effects and mechanism of puerarin targeting PI3K/Akt signal pathway on neurological diseases - Wang, Qian; Shen, Zi-Nuo; Zhang, Shu-Jing; Sun, Yan; Zheng, Feng-Jie; Li, Yu-Hang (Frontiers in Pharmacology, 2022)
Abstract: Neurological diseases impose a tremendous and increasing burden on global health, and there is currently no curative agent. Puerarin, a natural isoflavone extracted from the dried root of Pueraria montana var. lobata (Willd.) Sanjappa & Predeep, is an active ingredient with anti-inflammatory, antioxidant, anti-apoptotic, and autophagy-regulating effects. It has great potential in the treatment of neurological and other diseases. Phosphatidylinositol 3-kinases/protein kinase B (PI3K/Akt) signal pathway is a crucial signal transduction mechanism that regulates biological processes such as cell regeneration, apoptosis, and cognitive memory in the central nervous system, and is closely related to the pathogenesis of nervous system diseases. Accumulating evidence suggests that the excellent neuroprotective effect of puerarin may be related to the regulation of the PI3K/Akt signal pathway. Here, we summarized the main biological functions and neuroprotective effects of puerarin via activating PI3K/Akt signal pathway in neurological diseases. This paper illustrates that puerarin, as a neuroprotective agent, can protect nerve cells and delay the progression of neurological diseases through the PI3K/Akt signal pathway.